Evaluations of Market Orientations in Companies : contemporary methodological dilemmas and challenges - Fonfara, Krzysztof (Economics and Business Review, 2001)
The author´s goal in writing this article was to present an overview of possible approaches to and methods for evaluating a company´s market orientation. In formulating his conclusions, the author drew upon, among other things, the findings of the International Research Group, whose research and methodological objectives include developing methods for diagnosing companies in terms of their market orientations. (fragment of text)